Overview of Positioning Techniques for LTE Technology - Mahyuddin, M.F.M.; M.Isa, A.A.; Zin, M.S.I.M; A.H, Afifah Maheran; Manap, Z.; Ismail, M.K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper explains about the capabilities of location positioning in wireless broadband communications and potential of hybrid positioning which are based on long term evolution (LTE) system. Mobile positioning technology has become a widely used in condition such as emergency and also in commercial services. Nowadays, with the presence of LTE technology there is a new mission on enabling Enhanced 911 (E911) and location-based services (LBS) on these 4G/5G networks. The positioning methods that were supported for LTE technology are Enhanced Cell ID (E-CID) method, Observed Time Difference of Arrival (OTDOA) and Global Navigation Satellite Systems (GNSS). A hybrid positioning system is a combination of such technologies and improves positioning accuracy by implementing the different mechanisms of the different technologies. In particular, this paper describes a concept and principle of each technique and explores important technical details of the location positioning techniques.